BRISK WALKING EXERCISE ON ANXIETY IN PATIENTS WITH TYPE 2 DIABETES MELLITUS: AN EXPERIMENTAL STUDY - Naura Almaghfira Asy'ghotillah; Upik Rahmi; Sehabudin Salasa (Universitas Kadiri, 2026)
Anxiety is a psychological problem commonly experienced by patients with type 2 diabetes mellitus (T2DM) and can worsen glycemic control and increase the risk of complications. Brisk walking exercise, as a simple form of aerobic physical activity, is known to have potential metabolic and psychological benefits. However, empirical evidence regarding its implementation in primary healthcare settings is still limited. This study aimed to analyze the role of brisk walking exercise on anxiety levels in patients with T2DM. This study employed a quantitative method with a quasi-experimental pretest-posttest with control group design. The sample was selected using a purposive sampling technique, consisting of 40 respondents, divided into an intervention group (n=20) and a control group (n=20). The sample size was determined based on sample size calculation for experimental design. The intervention group received a brisk walking exercise program three times per week for eight weeks. Anxiety levels were measured using the Depression Anxiety Stress Scale-42 (DASS-42) questionnaire. Data were analyzed using paired t-test and independent t-test. The results showed that brisk walking exercise was associated with a reduction in anxiety levels in patients with T2DM compared to the control group. Brisk walking exercise can be considered as an effective nursing intervention to reduce anxiety in patients with T2DM.